2016
DOI: 10.1097/ico.0000000000001018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Superoxide Dismutase Activity, Malondialdehyde, and Zinc and Copper Levels in Patients With Keratoconus

Abstract: There is imbalance in the systemic oxidant/antioxidant status where Zn deficiency also plays a role in patients with keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…A 2012 study found increased superoxide dismutase (SOD) and reduced MMP-2 and zinc in KC patient blood (Ortak et al, 2012). However, this conflicts with a 2016 report which found no difference in SOD activity, although zinc was reduced in their cohort as well, corroborating a potential role for zinc deficiency (Kilic et al, 2016). Prolidase was found to be reduced in KC patient blood in a 2015 study which also found elevated oxidative stress markers (Goncu et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…A 2012 study found increased superoxide dismutase (SOD) and reduced MMP-2 and zinc in KC patient blood (Ortak et al, 2012). However, this conflicts with a 2016 report which found no difference in SOD activity, although zinc was reduced in their cohort as well, corroborating a potential role for zinc deficiency (Kilic et al, 2016). Prolidase was found to be reduced in KC patient blood in a 2015 study which also found elevated oxidative stress markers (Goncu et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Fenton reaction can generate the highly ROS implicating metals as iron or cupper increased in samples of keratoconus (iron ring at the basis of cone entitled Fleischer sign) (Rabinowitz 1998; Kiliç et al. 2016; Bamdad et al. 2018; Zarei‐Ghanavati et al.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this hypothesis, KC patients display lower serum levels of Cu, Se, and Zn [46,[59][60][61]. Moreover, Cu deficiency can be exacerbated in KC by increased tear alkalinity.…”
Section: Mineralsmentioning
confidence: 77%